“I am putting my fear on them subconsciously”: a qualitative study of contraceptive care in the context of abortion bans in the U.S. - Yasaman Zia; Erica Somerson; Connie Folse; Alejandra Alvarez; Kathryn Albergate Davis; Alison B. Comfort; Katherine Brown; Kristyn Brandi; Ghazaleh Moayedi; Cynthia C. Harper (Reproductive Health)
Abstract Background Since the Dobbs vs. Jackson Women’s Health Organization decision in June 2022, providers throughout the U.S. have been navigating the shifting legal landscape of abortion bans, which diminish the delivery of evidence-based healthcare. The Dobbs decision has had a detrimental impact on medical training, the physician–patient relationship, and provision of medical care. However, few studies have captured the effects on providers in adjacent fields, including contraceptive care. Our objective was to examine the impact of Dobbs on contraceptive care. Methods We conducted semi-structured in-depth interviews (August 2022–July 2024), with 41 contraceptive healthcare providers across the US, with the majority (63%) in abortion restrictive states. We utilized deductive thematic analysis to assess providers’ practice changes and experiences related to contraceptive services. Results In reaction to the Dobbs decision, providers noted increased requests for contraception, especially for highly effective methods. Providers worried that certain methods, such as IUDs or emergency contraception, would become restricted, and mentioned advance provision of pills and other ways that they would try to ensure supplies. Providers also discussed that their patients were worried about threats to contraception, including for adolescents. Some expressed concern, however, that the abortion bans may prompt providers to overemphasize high-efficacy methods with directive counseling. Providers shared that it was stressful to practice in contexts of uncertainty, with shifting abortion policies affecting contraceptive care, including emergent needs such as providing contraceptive services to out-of-state patients before they go home. Several providers shared that they felt an increased importance of their role in their communities, and a deepened commitment to advocate for their patients. Conclusions Abortion restrictions profoundly impact providers’ contraceptive counseling and care. The effects of Dobbs on providers and their clinical practices underscore providers' legally precarious position in today’s reproductive health landscape. Attention to contraceptive access and person-centered care has become a salient public health need across the U.S. The long-term impacts of limited reproductive rights may stretch an already under-resourced healthcare system and further emphasize moral pressures.